The Role of Agricultural Extenders in Empowering Nagari Siguntur Tua Farmers’ Group - Rivendri, Rivendri; Setiawati, Setiawati (Universitas Negeri Padang, 2023)
Agricultural extension workers are professionals responsible for providing guidance and assistance to farmers in improving agricultural productivity and welfare. They are an extension of the government or agricultural institutions in delivering information, technology, and skills to farmers. The objectives of this study are (1) to describe the role of agricultural extension workers in efforts to empower farmer groups. (2) Knowing the effect of the role of agricultural extension officers on the empowerment of farmer groups. Agricultural extension officers also play a role in coordinating agricultural activities at the local level, such as extension, training, and agricultural programme development. Apart from providing technical guidance, agricultural extension officers are also tasked with encouraging farmers to implement sustainable and environmentally friendly agricultural practices.